Penerapan Prinsip Good Governance Dalam Pelayanan Online Single Submission Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Nganjuk - Choirul Anam, Ayuntamara Sekar; Choirul Anam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
DPMPTSP Nganjuk Regency in improving quality services by being a pioneer in implementing an online service licensing system. The Online Single Submission (OSS) system was launched because the registration and permit application process can be done online, reducing bureaucracy and speeding up the licensing process and it is hoped that this will create a more conducive and highly competitive business environment. The success of OSS reflects a consensus between government, society and the private sector to achieve good governance. This research aims to determine and analyze the implementation of good governance and the driving factors as well as inhibiting factors in the implementation of good governance principles in the Nganjuk Regency Investment and One-Stop Integrated Services Service. Qualitative research methods. Data collection techniques include observation, interviews and documentation. The data analysis technique uses data analysis by Miles Huberman, & J. Saldana in Sugiyono (2018). The research results are based on indicators of the application of good governance principles according to Sedarmayanti (2013), namely optimal accountability, optimal transparency, participation that is not optimal, and the rule of law is quite optimal.